2020
DOI: 10.2174/2211536608666191026115045
|View full text |Cite
|
Sign up to set email alerts
|

Human Papillomavirus Infections, Cervical Cancer and MicroRNAs: An Overview and Implications for Public Health

Abstract: Human Papillomavirus (HPV) is among the most common sexually transmitted infections in both females and males across the world that generally do not cause symptoms and are characterized by high rates of clearance. Persistent infections due at least to twelve well-recognized High-Risk (HR) or oncogenic genotypes, although less frequent, can occur, leading to diseases and malignancies, principally cervical cancer. Three vaccination strategies are currently available for preventing certain HR HPVs-associated dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 181 publications
0
9
0
Order By: Relevance
“…Another form of classification is related to the carcinogenic potential of the HPVs-group 1 carcinogens (carcinogenic for humans), group 2A carcinogens (probably carcinogenic for humans), and group 2B carcinogens (potentially carcinogenic for humans) [16]. Of all high-risk HPVs, the most carcinogenic are HPV16 (approximately 50% of all cervical cancers are associated with this strain) and HPV18 because they are primarily involved in squamous epithelial lesions [19]. Infection with HPV is highly associated with sexual activity, non-sexual transmission, and transmission via fomites.…”
Section: Hpv: Structure Pathogenicity and Transformation Activitymentioning
confidence: 99%
“…Another form of classification is related to the carcinogenic potential of the HPVs-group 1 carcinogens (carcinogenic for humans), group 2A carcinogens (probably carcinogenic for humans), and group 2B carcinogens (potentially carcinogenic for humans) [16]. Of all high-risk HPVs, the most carcinogenic are HPV16 (approximately 50% of all cervical cancers are associated with this strain) and HPV18 because they are primarily involved in squamous epithelial lesions [19]. Infection with HPV is highly associated with sexual activity, non-sexual transmission, and transmission via fomites.…”
Section: Hpv: Structure Pathogenicity and Transformation Activitymentioning
confidence: 99%
“…MicroRNAs are small non-coding RNA molecules of 19–25 nucleotides that target and regulate a multitude of mRNAs [ 23 ]. The observation that these molecules’ expression is differentiated in several diseases, including cancer, has put a magnifying lens on them as possible biomarkers or therapeutic targets [ 24 , 25 ]. As far as HPV-related cervical cancer is concerned, it has been reported that HPV’s oncoproteins, E6 and E7, seem to target and modify the expression of a plethora of miRNAs, consequently intervening in cellular pathways [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…In general, microRNAs can regulate both the tumor suppressor and oncogenes genes and the altered expression of microRNAs represents an early event in the induction of carcinogenic by HPV infection [ 17 ]. Many studies show that in cervical cancer the expression of some microRNAs increases (miR-20a, miR-20b, miR-93, miR-224) and decreases in others (miR-127, miR-143/145, miR-218) [ 9 , 18 ]. Other studies have shown that miR-218 was higher in high-risk HPV + than in high-risk HPV negative carcinomas; furthermore, miR-146a levels were lower in p16INKa-positive (marker of high-risk HPV infection) than in p16INKa-negative samples [ 19 ].…”
Section: Introductionmentioning
confidence: 99%